Target discovery for immunotherapy of cervical cancer and high-risk human papillomavirus infection - Peng, X (2021)
Human papillomaviruses (HPVs) are small, double-stranded DNA viruses, and more than 170 types, including 15 types that are designated “high risk” (HR) or oncogenic, have been described. HR types are present in more than 99% of cervical cancers and each year, over 570,000 women are diagnosed with the disease causing 311,000 death per year worldwide. The emergence of cancer immunotherapy has provided new possibilities for the treatment of cancer. For this strategy, it is important to understand which proteins are presented on human leukocyte antigens (HLA) by the tumour and, therefore, could be recognised by T-cells and used as antigens in vaccination approaches or adoptive and recombinant T cell therapies.